Peran Profesionalitas ASN dalam Peningkatan Kualitas Pelayanan Publik Kantor Pertanahan Kota Gorontalo - Dengi Lalang, Hendrawana Nur; Wantu, Sastro M; Igirisa, Irawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the impact of civil servant (ASN) professionalism on public service quality at the Gorontalo City Land Office. The background is rooted in the strategic role of ASN in ensuring legal certainty of land ownership and efforts to enhance accountable, responsive public services. A quantitative survey method using stratified random sampling was applied to all civil servants, supported by multiple linear regression analysis to examine the contributions of professionalism dimensions—competence, integrity, ethics, innovation, and responsibility—to service quality. The results show ASN professionalism is generally good, with competence and integrity as dominant factors, while innovation remains low. Regression analysis reveals ASN professionalism contributes 48% to the variation in public service quality, with the remaining influenced by additional factors such as regulations, infrastructure, and technology. The practical implication is the necessity to strengthen technical capacity, promote service ethics, and develop digital innovation, ensuring effective bureaucratic reform in the land sector. The study recommends strategies to improve ASN development and process transparency to foster greater community trust and satisfaction.